Self Potential Modeling for Investigation of Shallow Structure in Volcanic Region: a Study Case at Domas Crater, Tangkuban Parahu Volcano, West Java - Wahyu Srigutomo; Alamta Singarimbun; Adhitya S. Sunarya; Prihandhanu M. Pratomo; Anggie Susilawati; Candra E. Novana; Deny Juanda Puradimaja; Eleonora Agustine (Indonesian Journal of Physics, 2010)
Quantitative numerical modeling of self-potential (SP) anomaly associated with subsurface electric current density that is attributed to cross-coupling between fluid flow and electrical conductivity distributions has been conducted. The modeling scheme was applied to an area in the vicinity area of Domas crater, Tangkuban Parahu volcano in West Java. The field surveys at domas were conducted from mid-2008 until mid-2009. The main objective of this researchis to obtain a quantitative model that is possible to explain the shallow convective hydrothermal system in the eastern side of the volcano by making comparison between SP anomaly measured on the surface with theoretical anomaly resulted from modeling. Since the modeling scheme requires information on the subsurface resistivity structure, we performed measurement and interpretation of 2-D resistivity at Domas crater. The measurement of CO2 emission that is commonly associated with magmatic gas migration patterns through fracture system was also carried out on the same SP and resistivity lines. Fluid velocity vector was calculated by solving the coupled Darcy’s and energy equations involving heat transfer terms by both convection and conduction. The subsurface electric current source distribution was calculated by solving the coupled equation of velocity and potential gradients. The results show that the fluid flow patterns around Domas Crater which in addition is controlled by topographic effect; it is also influenced by thermal fluid flows through relatively high permeability zone beneath the Domas Crater.